The Role of Working Children in Helping the Income of Poor Fishermen Families in Nelayan Indah Village, Medan Belawan District - Intan Natalya; Humaizi Humaizi; Bengkel Ginting (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2026)
The phenomenon of working children remains prevalent among poor fishing communities, including those in Neighborhood III of Nelayan Indah Village, Medan Labuhan District. Economic limitations and unstable income from fishing activities encourage children to participate in income-generating activities to support household needs. This study aims to analyze how working children divide their time between school and work, examine their economic contribution to family income, and explore community perceptions regarding child labor in poor fishing households. The research employed a qualitative descriptive approach. Data were collected through in-depth interviews, observation, and documentation involving working children, parents, community members, business owners, and local government officials. The findings indicate that children generally perform work activities outside school hours, enabling them to continue their formal education while contributing economically to their families. Although the income earned by children is relatively small, it functions as supplementary income that helps reduce household economic burdens. Community members generally perceive children’s involvement in work as acceptable and reasonable due to persistent poverty, unstable fishing incomes, and a cultural tradition of helping parents. The study concludes that child labor among poor fishing families is closely associated with household survival strategies and structural poverty, while education remains an important aspiration for children and their families despite economic constraints.